NOUVELLE TECHNIQUE DE TRANSFORMATION DE LA PULPE DE MANIOC (Manihot esculenta CRANTZ) SOUS FORME DE GRANULES CONSERVABLES SUR UNE LONGUE PERIODE - Yao, Augustin Koffi; Koffi, Djary Michel; Blei, Sika Hortense; Irié, Zaouli Bi; Niamké, Sébastien Lamine (European Scientific Journal, ESJ, 2015)
To solve the problem of conservation of fresh cassava, native cassava granules have been produced with three cultivars: bonoua, soglo and yacé. These granules made by drying the crushed, pressed and packaged in polyethylene bags 160 µm thick has been stored for two years at ambient temperature. The biochemical and microbiological analyses carried on the granules before and after preservation for two years have shown no significant change on the biochemical composition. These granules contain 10% humidity,84 % total carbohydrate, of which 55 % starch, 29 % total sugars including 20 % reducing sugars. These granules have been stable for the point of view of biochemical composition and the microbial content and did not contain cyanhydric acid. No browning reaction has been observed during preservation hence the granules have kept the colour of fresh cassava